THE EFFECT OF INDEPENDENT COMMISSIONERS, COMPANY SIZE AND PROFITABILITY ON TAX AVOIDANCE IN COMPANIES LISTED IN THE IDX80 INDEX OF THE INDONESIA STOCK EXCHANGE - Muklas Nur Ardiansyah; Sri Zulaihati; Mardi Mardi (Yayasan Education and Social Center, 2023)
This study aims to analyze the Effect of Independent Commissioners, Company Size and Profitability on Tax Avoidance in Companies Listed in the IDX80 Index of the Indonesia Stock Exchange. The research method used is a quantitative method with secondary data obtained by collecting the annual financial statements of IDX80 companies on the Indonesia Stock Exchange page. The research sample was 57 IDX80 companies selected using a purposive sampling technique. The data analysis technique used is descriptive statistics, analysis prerequisite test, classical assumption test, multiple linear regression test and hypothesis testing. The results of this study indicate that independent commissioners have no effect on tax avoidance, company size harms tax avoidance and profitability has no effect on tax avoidance. The coefficient of determination in this study is 6%, indicating independent commissioners' ability, company size and profitability to affect tax avoidance. At the same time, the rest is influenced by other factors not examined